Attitudes toward Science Based on Analysis and Correlation: Learning Enjoyment & Leisure Interest on Science - Tanti Tanti; Dwi Agus Kurniawan; Nugroho Kurniawan; Lika Anggraini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
This study aims to investigate attitudes towards science in junior high school students, which are assessed based on 2 attitude indicators: (1) enjoyment in science lesson & (2) leisure interest in science. In addition, measurements were also made regarding the relationship between the two indicators of attitude. Research method: This research is survey research. The results of the data came from an attitude questionnaire consisting of indicators (1) enjoyment in science lesson and (2) leisure interest in science. The sample consisted of 2815 Secondary School students in Jambi Province, Indonesia. Finding: The results showed positive results, based on the investigation concluded that for indicators: (1) enjoyment in science has a good category with a percentage of 48.1%, (2) leisure interest in science has a fairly good category with a value: 47.2% and This indicator leads to a positive trend supported by a positive attitude with a greater good value: 38.4%, while for the analysis of the correlation between the two indicators shows a positive correlation with a sig: 0,000 (<0.05) and has a strong degree of correlation indicated by the value